Juridical Review of Granting Licenses for Analysis of Environmental Impact in The Environmental Office of Boyolali District - Safira El Ulya Wahid; R Rizka (Universitas Muhammadiyah Surakarta, 2023)
The environment plays a role in everyday life, so environmental protection and management is needed. This research contains a juridical review of granting AMDAL permits at the Boyolali Regency environmental service. This research aims to determine the granting of AMDAL permits in Boyolali Regency and to determine the implementation of granting AMDAL permits in Boyolali Regency. This research uses normative and empirical research. The data in this research uses literature study and direct interviews with the Environmental Service. The results of this research explain the preparation of AMDAL through several stages, including screening, scoping, preparation of KA-ANDAL, preparation of ANDAL, preparation of environmental management plans, preparation of environmental monitoring plans and reporting. The implementation of AMDAL permits in Boyolali Regency includes the construction of a mall, hotel and Grand Maharani business center, construction of the Asy Syifa Sambi general hospital, and development of the PKU 'Aisiyah Boyolali hospital.